Avaliação da eficácia das recomendações do Tribunal de Contas do Estado para melhoria da qualidade da educação básica municipal - Frederico, Maristela (2020)
Public and quality education is a fundamental right constitutionally protected and a duty of the State with the population delegating the power to govern. Access to education enables the participation of society in the planning of Public Policies, in the formation of the political agenda and, especially, in the control of the effectiveness and quality of Educational Policy. The measurement of educational quality in Brazil is accomplished by the Basic Education Development Index, originated from the Ministry of Education and made by the National Institute of Educational Studies and Research. In order to realize the right to education, the Federal Constitution of 1988 binds a percentage of public revenue that must be applied by government officials. External controls, notably the Court of Accounts of Paraná, control the application of these resources and one of the forms of monitoring is through the Municipal Management Effectiveness Index. This index assesses whether public management is effective in seven dimensions, among which is education. This research evaluates the association between the Municipal Management Effectiveness Index, in the Education dimension and the improvement of educational quality, in the cities of Paraná, in the period 2016-2017. It is an exploratory research, with a qualitativequantitative approach, with the analysis of the secondary data that compose the two indexes and with the use of statistical tools of econometrics, through the techniques of linear regression and factor analysis. The results point to the existence of a relationship between the indicators that make up the Municipal Management Effectiveness Index, in the Education dimension and educational development, with regard to FUNDEB resources, establishments and teachers for pre-school enrollments, training hours and resources applied in teaching. Thus, the effectiveness of the recommendations of the State Audit Courts will be associated with the improvement of educational quality when linked to the implementation of these public policies of municipal basic education.